2022
DOI: 10.3390/children9111770
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence, Physical Activity Practice and Mediterranean Diet Adherence-An Explanatory Model in Elementary Education School Students

Abstract: Currently, there is a global concern with regard to the lifestyles of young people. This study aims to study the association between Mediterranean diet adherence, emotional intelligence and physical activity practice in teenagers in the last cycle of elementary education. In turn, this objective is divided into (a) developing an explanatory model of the practice of physical activity, Mediterranean diet adherence and emotional intelligence; and (b) developing a multi-group model according to the gender of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In parallel to this study, children who participated in organised sport activity more than three hours daily reported better intrapersonal and interpersonal levels, emotional intelligence and stress management than those who did not [ 51 ]. A very different result has been found by Melguizo-Ibáñez et al, 2022, who reported a negative association between PA and emotional intelligence among female elementary school students [ 52 ]. A previous study among obese children found a negative association between the degree of obesity and quality of life [ 53 ].…”
Section: Discussionmentioning
confidence: 72%
“…In parallel to this study, children who participated in organised sport activity more than three hours daily reported better intrapersonal and interpersonal levels, emotional intelligence and stress management than those who did not [ 51 ]. A very different result has been found by Melguizo-Ibáñez et al, 2022, who reported a negative association between PA and emotional intelligence among female elementary school students [ 52 ]. A previous study among obese children found a negative association between the degree of obesity and quality of life [ 53 ].…”
Section: Discussionmentioning
confidence: 72%
“…In contrast, research by Ferrer-Cascales et al [41] found a better conception of emotional and dietary states for females. Similarly, Melguizo-Ibáñez et al [42] found that female teenagers showed greater emotional competence than males.…”
Section: Discussionmentioning
confidence: 89%
“…Numerous studies have suggested that adolescent populations are becoming increasingly sedentary [47,48]. Numerous studies have affirmed that the educational field must provide a comprehensive education, in which the complete development of the student is achieved [34,42,49]. It has been found that, apart from the educational environment, there are other variables that can condition the acquisition of an active and healthy lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…Estévez et al [27] claim that emotional intelligence exerts a buffering effect on disruptive behaviour [27]. This means that more emotional training reduces violent disruptive behaviour [28,29].…”
Section: Discussionmentioning
confidence: 99%